Diversity of avian species in peri-urban landscapes surrounding Fez in Morocco: species richness, breeding populations, and evaluation of menacing factors - Squalli, Wafae; Mansouri, Ismail; Douini, Ikram; Achiban, Hamid; Fadil, Fatima; Dakki, Mohamed; Wink, Michael (Diversity, 2022)
In this study, we investigated the avian diversity and threatening factors in five peri-urban sites around Fez city (Morocco) for 2 years (2018-2019). The study hosted 131 avian species, including 64.88% breeding species, 19.84% migrant winterers, and 11.45% migrant breeders. Five species of conservation concern such as the vulnerable European turtle dove and the European goldfinch, the near-threatened ferruginous duck and bar-tailed godwit, and the endangered white-headed duck were recorded. Most bird species were recorded at the Oued Fez River (26.89%) and the El Mehraz dam (25%), followed by the El Gaada dam (17.4%), the Ain Bida garbage dump (15.5%), and the Ain Chkef Forest (15.18%). About 44.44% of the breeding species were found at Oued Fez, along with 33.33% at the El Mehraz dam, while El Gâada, Ain Chkef, and Ain Bida hosted only 7.40% of species. An important breeding population of the endangered white-headed duck was recorded at El Mehraz and Oued Fez. The extension of farmlands, urbanization, touristic activities, and drought constitute the most menacing factors for the avian diversity and their habitats in Fez.
Gesehen am 11.01.2023
This article belongs to the special issue "Diversity in 2022"